The Lebanese press in opposition to the French in 1943: The (??) newspaper, two question marks as a model - Al Zuhairi, Assis. Prof. Dr. Hussein Abdel Hussein Abbas; Jabr, Ass,Prof. Dr. Haider Abdel-Aali (Thi Qar Arts Journal, 2022)
The Lebanese press played a major role in directing Lebanese public opinion; As the only carrier of political, economic and social events and developments in Lebanon, this press, whose roots go back to the mid-nineteenth century, was able, thanks to its extensive experience, to control the Lebanese with their various orientations, tendencies and sects, and the press was able to form a strong opposition to the French trends, especially during the crisis The eleventh of November 1943, whose effects were clearly reflected on the developments of the Lebanese political situation in general, and on the French in particular. The subject of the Lebanese press in opposition to the French was not previously discussed by researchers in their academic and scientific studies, which makes it of great importance to shed light on it, and herein lies the importance of the subject.In this research, we focused on (the Lebanese press opposed to the French in 1943: the newspaper (??) two question marks as a model), which was chosen in 1943; As the year in which the newspaper appeared for the first time, as a result of political developments in Lebanon, after the French authorities suspended all newspapers and publications in Lebanon, following the declaration of martial law in November of that year. The researcher stopped in 1943; Having witnessed the abolition of all the laws issued by the French authorities in Lebanon by the Lebanese Parliament, including the law of disabling the press and publications, as well as the end of the Lebanese crisis, the return of political life to normal, and the extinction of the newspaper whose name was later changed to Al-Aqdam newspaper. This important media outlet appeared with the crisis and ended with its end, and it was the medium that conveyed to all the Lebanese the course of political events in their country after all the newspapers stopped, and it is issued in secret.